2016
DOI: 10.1097/mcp.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea during rapid eye movement sleep

Abstract: Purpose of review Obstructive sleep apnea (OSA) is a highly prevalent condition that has been associated with cardiovascular morbidity and mortality, impaired glucose metabolism and daytime functional impairment. Compared with non-rapid eye movement (NREM) sleep, rapid eye movement (REM) sleep is associated with higher sympathetic activity and cardiovascular instability in healthy individuals and more so in patients with OSA. Recent findings Recent studies have indicated that REM OSA is independently associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…The longest percentage of REM was below 15.68%. It corresponds to a clinical study that estimated the prevalence percentage of REM in the SDB patients (such as OSA patients) was around 13.5% [59], and we obtained below 15.68%.…”
Section: Resultssupporting
confidence: 81%
“…The longest percentage of REM was below 15.68%. It corresponds to a clinical study that estimated the prevalence percentage of REM in the SDB patients (such as OSA patients) was around 13.5% [59], and we obtained below 15.68%.…”
Section: Resultssupporting
confidence: 81%
“…As other authors have suggested, 10,[18][19][20] we propose that individuals with several apneas and hypopneas during REM sleep, even with milder OSA forms, could benefit from treatment to reduce harmful effects to brain health. Consistently, continuous positive airway pressure (CPAP) was previously shown to be effective in reversing at least partially daytime rCBF changes in OSA individuals.…”
Section: Clinical Significance Of Rem Sleep Osamentioning
confidence: 68%
“…Although groups are clinically important, there is many different criteria that exist in the current literature with arguably arbitrary cut-offs to define the presence of REM sleep OSA. 10 Moreover, some studies showed a dose-response relationship between various physiological functions and respiratory events during REM sleep. [18][19][20][21] Regression models are not limited by arbitrary cut-offs and may represent more closely the physiopathology compared to a group analysis.…”
Section: Use Of a Regression Approach In Rem Sleep Osamentioning
confidence: 99%
See 2 more Smart Citations